2019
DOI: 10.25011/cim.v42i1.32390
|View full text |Cite
|
Sign up to set email alerts
|

RIPK3 expression as a potential predictive and prognostic marker in metastatic colon cancer

Abstract: Background: Colorectal cancer is one of the primary causes of cancer-related deaths and 5-fluorouracil (5-FU) therapy remains the cornerstone of treatment in these patients. Resistance to 5-FU represents a major obstacle; therefore, finding new predictive and prognostic markers is crucial for improvement of patient outcomes. Recently a new type of programmed cell death was discovered—necroptosis, which depends on receptor interacting protein 3 (RIPK3). Preclinical data showed that necroptotic cell death is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…Briefly, both pro- and anti-tumoral effects have been demonstrated following necroptosis in cancer development and progression. The anti-tumoral effect of necroptosis has been shown in many types of cancer in which the expression of RIPK3 66,67 or MLKL 68 was silenced or polymorphisms in their coding genes lead to modified expression of necrosomal components 66,69 . In general, necroptosis resistance of cancer cells is a common process, and escape from necroptosis was suggested to be a potential hallmark of cancer, similar to the escape from apoptosis 64 .…”
Section: Necroptosis Involved In Human Diseasesmentioning
confidence: 99%
“…Briefly, both pro- and anti-tumoral effects have been demonstrated following necroptosis in cancer development and progression. The anti-tumoral effect of necroptosis has been shown in many types of cancer in which the expression of RIPK3 66,67 or MLKL 68 was silenced or polymorphisms in their coding genes lead to modified expression of necrosomal components 66,69 . In general, necroptosis resistance of cancer cells is a common process, and escape from necroptosis was suggested to be a potential hallmark of cancer, similar to the escape from apoptosis 64 .…”
Section: Necroptosis Involved In Human Diseasesmentioning
confidence: 99%
“…SART3 has been shown to induce both a humoral and cellular adaptive immune response in a vaccination study of patients with advanced colorectal cancer 67 . RIPK3 is a tumor suppressor whose downregulation has been associated with tumorigenesis, immunomodulation, and poor clinical prognosis in colorectal cancer 68,69 , although its exact role in the adaptive immunity is still under investigation. While confirmatory studies are needed, the present study in conjunction with supporting studies in other cancer types nominates potential immune biomarkers and therapeutic targets in mCRPC.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the relationship of pro-necroptotic molecules' gene-expression with cancer patient's prognosis seems to be highly context-dependent. For example, the analysis of RIPK3 expression in 74 primary CRC tumors treated with first-line 5-fluorouracil (5-FU) chemotherapy revealed that high expression levels of RIPK3 correlated with a significantly longer overall survival and lower risk of disease progression in CRC patients [208]. Consistent with this, low expression of RIPK1 was correlated with, higher tumor progression in head and neck squamous cell carcinoma (HNSCC) patients [209] and worse prognosis in human hepatocellular carcinoma (HCC) patients [210].…”
Section: Sp1mentioning
confidence: 99%
“…Longer mean overall survival after treatment with 5-fluorouracil (5-FU) [208] Low expression Breast cancer Worse prognosis [201] Colon rectal cancer (CRC) Worse overall survival and disease-free interval. [202] RIPK1 expression…”
Section: Ripk3 Expressionmentioning
confidence: 99%